2005
DOI: 10.1074/jbc.m501290200
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Mitogen-activated Protein KinaseErk1/2 Activation and Non-selective Pore Formation in P2X7 Receptor-mediated Thymocyte Death

Abstract: Extracellular ATP (ATPe) binds to P2X7 receptors (P2X7R) expressed on the surface of cells of hematopoietic lineage, including murine thymocytes. Activation of P2X7R by ATPe results in the opening of cation-specific channels, and prolonged ATPe exposure leads to the formation of non-selective pores enabling transmembrane passage of solutes up to 900 Da. In the presence of ATPe, P2X7R-mediated thymocyte death is due primarily to necrosis/lysis and not apoptosis, as measured by the release of lactate dehydrogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 63 publications
5
66
1
Order By: Relevance
“…In addition, ␣-fodrin degradation is proposed to contribute to cell blebbing and other morphologic changes (40). Extracellular ATP stimulation is also reported to induce c-Src activation and tyrosine phosphorylation of intracellular proteins (41,42). However, we could not detect degradation in cytoskeletal proteins including ␣-fodrin, actin, c-Src, and Pyk2.…”
Section: Extracellular Atp Alters the Pattern Of Pyk2 Distribution Incontrasting
confidence: 51%
“…In addition, ␣-fodrin degradation is proposed to contribute to cell blebbing and other morphologic changes (40). Extracellular ATP stimulation is also reported to induce c-Src activation and tyrosine phosphorylation of intracellular proteins (41,42). However, we could not detect degradation in cytoskeletal proteins including ␣-fodrin, actin, c-Src, and Pyk2.…”
Section: Extracellular Atp Alters the Pattern Of Pyk2 Distribution Incontrasting
confidence: 51%
“…In contrast, Auger et al (9) reported that ERK1/2 phosphorylation plays a role in P2X 7 receptor-mediated necrotic cell death, and these events are independent of pore formation. Thus, we investigated the contributions of cell shrinkage and the ERK1/2 pathway to P2X 7 receptor-mediated splenocyte death.…”
Section: Dual Signaling Pathways Of P2x 7 Receptor-mediated Cell Deathmentioning
confidence: 94%
“…The P2X 7 receptor C-terminal region of C57BL/6 mice bears a Pro-451 to Leu mutation that impairs nonselective pore formation (30), but there are no differences between the two mouse strains in terms of P2X 7 receptor mRNA and protein expressions, and ATP-induced phosphorylation of ERK1/2 (9). Reduced sensitivity to ATP-induced pore formation, cell shrinkage, and cell death were observed in splenocytes from C57BL/6 mice compared with BALB/c mice (Fig.…”
Section: P2x 7 Receptor-mediated Cell Shrinkage In Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other important functions where P2X7 has been implicated include killing of mycobacteria and Chlamydia residing inside macrophages [33][34][35], apoptosis of immune cells [14,36,37], cell fusion [38,39] and shedding of the CD62L homing receptor and other membrane proteins including CD23 and CD27 [14,40,41].…”
Section: Introductionmentioning
confidence: 99%